Cost outcomes of potentially inappropriate prescribing in middle‐aged adults: A Delphi consensus and cross‐sectional study. Issue 7 (18th March 2022) - Jayesinghe, Ryan; Moriarty, Frank; Khatter, Amandeep; Durbaba, Stevo; Ashworth, Mark; Redmond, Patrick
Abstract : Background: Potentially inappropriate prescribing (PIP) is common in older adults and is associated with increased medication costs and costs of associated adverse drug events. PIP also affects almost 1/5 of middle‐aged adults (45–64 y), as defined by the PRescribing Optimally in Middle‐aged People's Treatments (PROMPT) criteria. However, there has been little research on PIP medication costs within this age group. Aims: Calculate the medication costs of PIP for middle‐aged adults according to the 22 PROMPT criteria and compare with the cost of consensus‐validated, evidence‐based ( adequate ) alternative prescribing scenarios. Methods: Adequate alternatives to the 22 PROMPT criteria were created via literature review. A Delphi consensus panel of experts was recruited ( n = 16), supported by a patient and public involvement group, to achieve consensus on the alternatives. A retrospective repeated cross‐sectional study from 2014 to 2019 was then conducted utilising pseudonymised primary care data from Lambeth DataNet in South London (41 general practices, n = 1 185 335, using Lambeth DataNet May 2020 extract) to calculate the cost of PIP. Results: The cross‐sectional study included 55 880 patients. The total PIP cost was £2.79 million, with adequate alternative prescribing costing £2.74 million (cost savings of £51 278). Duplicate drug classes was the most costly criterion for both PIP and alternative prescribing. Conclusion: This study calculated the medication costs of PIP and created alternative prescribing scenarios for the 22 PROMPT criteria. There is no substantial cost difference between adequate prescribing vs . PIP. Future studies should investigate the wider health economic costs of alternative prescribing, such as reducing hospital admissions.